An evaluation of e-learning implementation during COVID-19 emergency response period - Eka Nur Rahayu (International Journal of Evaluation and Research in Education (IJERE), 2022)
Implementation of educational programs during the coronavirus emergency about online learning and working from home in the context of preventing the spread of coronavirus disease (Covid-19). Even semester learning is organized according to the needs of each tertiary institution. Learning activities must be evaluated on issues such as reliability, effectiveness, cost-effectiveness, efficiency, security, ease of use, and honesty. Evaluation is needed to give information about deficiencies in the design of implementation systems, which will produce direction for learning improvement. This type of research is research that conceptualized the mix-method approach to find out how the implementation of e-learning/online learning during the COVID-19 emergency response at the AKBIDYO Schools of Health Sciences with a sample of 152 people. The research instrument was a questionnaire given to ACTION model students from Bates (1995). Virtual-based learning is more easily understood by students supported by digital documents, and other e-learning tools. Barriers to students in participating in e-learning learning is an internet connection. Lecturers must plan e-learning well.